International Sanctions and Labor Emigration: A Case Study of Iran - Afsaneh Zareei; Mohammad Ali Falahi; Eskil Wadensjö; Saeed Malek Sadati (Institute of Labor Economics (IZA), 2024)
Sanctions have severe adverse effects on societies. Even though sanctions are used against governments, the population is punished for its government's behavior. Sanctions can create problems due to international migration. Iran is an unique case study because it faced the most and hardest sanctions in the world until February 2022. Many negative effects on the economy have been observed such as losing the Rial's value against the US Dollar by 80 percent, increasing poverty, and reducing exports and imports. At the same time, Iran had a very fast growth of emigration with an increase of 141 percent. Sanctions have been imposed on Iran's economy in different ways, but so far, it has not been determined how each type of sanctions will affect emigration. The aim of this study is to study the relationship between different kinds of economic sanctions and labor emigration using the Dynamic Stochastic General Equilibrium model. Different types of sanctions as oil and nonoil exports and three different import sanctions on consumer, capital, and intermediate goods are considered. The results show that sanctions on nonoil exports are most influencing emigration. Sanctions on the imports of intermediate and consumer goods, as well as sanctions on oil exports, are in the next steps, but not as much as the non-oil exports. It can be noticed that out of approximately 24 million people working in Iran, up to 4 percent of the working force have a desire to leave the country as migrant workers due to the sanctions.
Keywords: B22; C02; C11; C68; F22; P00; 330; international sanctions; labor emigration; DSGE Models; Iran